KAWRUH JIWA SURYOMENTARAM: KONSEP EMIK ATAU ETIK? - Nilam Widyarini (Faculty of Psychology Universitas Gadjah Mada, 2008)
The concept of happiness or healthy personality was born through the enlightening personal experiences of Suryomentaram after his decision to leave Mataram royal family to become the common people. Written in Javanese the concept is often considered as an emic concept which is applied only for Javanense. In contrast, the author argues that Suryomentaram’s concept of “kawruh jiwa” is an etic and universal concept. The argument is based on the similarity when comparison is made between some Suryomentaram’s concepts and several Western psychological concepts. This article reviews the conceptual comparison and describes the contribution of Suryomentaram’s concepts to psychology and related sciences.